E-professionalism assessment instruments in healthcare professionals: a systematic review protocol - Fernando de Castro Araújo-Neto; Lívia Gois dos Santos; Thaís Maria Araújo Tavares; Douglas de Menezes Santos; Divaldo Pereira de Lyra-Jr (BMJ Open)
Introduction Social media has an impact on the reach and speed with which information is disseminated, benefiting patients and healthcare professionals by sharing knowledge, even from a distance. However, these channels can pose risks when used irresponsibly by these actors. Thus, e-professionalism emerges as a modulator of professionals’ behaviours and attitudes, and its evaluation is fundamental given the demand for quality in services, including in these settings. Thus, this study aims to identify instruments used to assess the e-professionalism of healthcare professionals.Methods and analysis A systematic review will be developed to answer the question: ‘How is e-professionalism in healthcare professionals evaluated in the literature?’. The searches will take place in the following databases: PUBMED/Medline, EMBASE, Web of Science, ERIC and Scopus using descriptors such as ‘professionalism’, ‘e-professionalism’, ‘social media’ and synonyms. Studies will be selected after evaluating titles and abstracts, followed by an analysis of full texts using the Rayyan tool. Studies that present the development and validation of e-professionalism assessment instruments for nursing, pharmacy, medicine and dentistry will be included. The quality of the instruments will be assessed based on evidence of content and construct validity reported by the developers.Ethics and dissemination This review is exempt from ethical approval because it does not include patient data. The results of the systematic review will be disseminated through a peer-reviewed journal and presented at a relevant conference.PROSPERO registration number CRD42023454825.